Implementation Multi Factor Evaluation Process (MFEP) Decision Support System for Choosing the Best Elementary School Teacher - Herlina Usman, S Sriyanto, Achmad Buchori Arri Handayani, Phong Thanh Nguyen (International Journal of Control and Automation, 2020)
Education is the main priority for the nation and state. Education is formed when someone attends elementary school. Good education requires good teachers too. Public elementary schools are one of the primary schools that must have qualified teachers. This study discusses how to measure the performance of teachers working in these schools. To improve teacher performance and quality, a decision support system is needed to measure the quality of the teacher. The MFEP method is one method that can measure teacher performance. This method works by calculating five criteria as a basis for measuring teacher quality. The results of this method are the order of teacher achievement from highest to lowest. The benefits obtained, the school can develop teacher quality based on the results of the MFEP trial method.